A call for differentiated approaches to delivering HIV services to key populations. (21st July 2017) - Macdonald, Virginia; Verster, Annette; Baggaley, Rachel
Abstract: Introduction : Key populations (KPs) are disproportionally affected by HIV and have low rates of access to HIV testing and treatment services compared to the broader population. WHO promotes the use of differentiated approaches for reaching and recruiting KP into the HIV services continuum. These approaches may help increase access to KPs who are often criminalized or stigmatized. By catering to the specific needs of each KP individual, differentiated approaches may increase service acceptability, quality and coverage, reduce costs and support KP members in leading the HIV response among their communities. Discussion : WHO recommends the implementation of community‐based and lay provider administered HIV testing services. Together, these approaches reduce barriers and costs associated with other testing strategies, allow greater ownership in HIV programmes for KP members and reach more people than do facility‐based services. Despite this evidence availability and support for them is limited. Peer‐driven interventions have been shown to be effective in engaging, recruiting and supporting clients. Some programmes employ HIV‐positive or non‐PLHIV "peer navigators" and other staff to provide case management, enrolment and/or re‐enrolment in care and treatment services. However, a better understanding of the impact, cost effectiveness and potential burden on peer volunteers is required. Task shifting and non‐facility‐based service locations for antiretroviral therapy (ART) initiation and maintenance and antiretroviral (ARV) distribution are recommended in both the consolidated HIV treatment and KP guidelines of WHO. These approaches are accepted in generalized epidemics and for the general population where successful models exist; however, few organizations provide or initiate ART at KP community‐based services. Conclusions : The application of a differentiated service approach for KP could increase the number of people who know their status and receive effective and sustained prevention and treatment for HIV. However, while community‐based and lay provider testing are effective and affordable, they are not implemented to scale. Furthermore regulatory barriers to legitimizing lay and peer providers as part of healthcare delivery systems need to be overcome in many settings. WHO recommendations on task shifting and decentralization of ART treatment and care are often not applied to KP settings.